2013
DOI: 10.1186/1475-2875-12-459
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pfcrt 72-76 haplotypes eight years after chloroquine withdrawal in Kinshasa, Democratic Republic of Congo

Abstract: BackgroundIn 2001, the World Health Organization (WHO) has recommended the use of artemisinin-based combination therapy (ACT) as the first-line treatment of uncomplicated malaria cases, as monotherapies had become ineffective in many parts of the world. As a result, the Democratic Republic of Congo (DRC) withdrew chloroquine (CQ) from its malaria treatment policy in 2002 and an artesunate (AS)-amodiaquine (AQ) combination became the ACT of choice in DRC in 2005. AQ-resistance (AQR) has been reported in several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 31 publications
(35 reference statements)
3
31
1
Order By: Relevance
“…Such a shift in the parasite population after the interruption of CQ use has been observed in several countries in Africa 10, 12, 13, 36 . This reversal to the wild type form of the PfCRT gene indicates that parasites carrying the mutant PfCRT may have a substantial fitness cost in the absence of CQ, thus leading to their decline in frequency once drug pressure is removed 14 .…”
Section: Discussionmentioning
confidence: 65%
“…Such a shift in the parasite population after the interruption of CQ use has been observed in several countries in Africa 10, 12, 13, 36 . This reversal to the wild type form of the PfCRT gene indicates that parasites carrying the mutant PfCRT may have a substantial fitness cost in the absence of CQ, thus leading to their decline in frequency once drug pressure is removed 14 .…”
Section: Discussionmentioning
confidence: 65%
“…However, this prevalence was higher in other sites such as Bolenge (32%), Vanga (41.3%), Kinshasa (48.8%) and especially at Katana (89.5%). Previous studies have reported much higher K76T rates in Kinshasa in 2008 (83.8%)[31] and 2010 (73.2%)[21], and in Bolenge in 2014 (70.6%)[22].The simultaneous presence of very low and high prevalence of CQ resistance could be related to different levels of CQ pressure between study sites, differing from one site to another, before and after the withdrawal of this molecule. Concerning the use of CQ in DRC, data from the DHS II in 2013-2014 revealed that in provinces where our sites are located (before territorial apportionment from 11 to 26 provinces) CQ was still in use despite its withdrawal from the national policy of malaria management in 2001[32].…”
mentioning
confidence: 78%
“…Chloroquine resistance continues to persist in most countries affected by malaria [32], and the DRC is not spared. Indeed, after removing chloroquine from the DRC's malaria treatment policy 11 years ago, still, Juliao et al [32] and Mvumbi et al [33] have identified markers of chloroquine resistance.…”
Section: Introductionmentioning
confidence: 99%